2018
DOI: 10.1128/cmr.00084-16
|View full text |Cite
|
Sign up to set email alerts
|

Options and Limitations in Clinical Investigation of Bacterial Biofilms

Abstract: Bacteria can form single- and multispecies biofilms exhibiting diverse features based upon the microbial composition of their community and microenvironment. The study of bacterial biofilm development has received great interest in the past 20 years and is motivated by the elegant complexity characteristic of these multicellular communities and their role in infectious diseases. Biofilms can thrive on virtually any surface and can be beneficial or detrimental based upon the community's interplay and the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
143
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(147 citation statements)
references
References 484 publications
(437 reference statements)
0
143
1
3
Order By: Relevance
“…Although much of the direct antibacterial activity of MSC involving production of AMPs has been previously reported, little has been noted previously regarding the ability of MSC to disrupt preexisting bacterial biofilms . Here, we also report that newly forming or already formed biofilms can be disrupted by MSC, highlighting the potential for MSC to be used as a treatment for chronic infections, including those often associated with biofilms . We also found that MSC produced factors that enhance the bactericidal activity of all major classes of antibiotics evaluated, including enhancement of antibiotic activity against MDR bacteria.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Although much of the direct antibacterial activity of MSC involving production of AMPs has been previously reported, little has been noted previously regarding the ability of MSC to disrupt preexisting bacterial biofilms . Here, we also report that newly forming or already formed biofilms can be disrupted by MSC, highlighting the potential for MSC to be used as a treatment for chronic infections, including those often associated with biofilms . We also found that MSC produced factors that enhance the bactericidal activity of all major classes of antibiotics evaluated, including enhancement of antibiotic activity against MDR bacteria.…”
Section: Discussioncontrasting
confidence: 58%
“…39 Here, we also report that newly forming or already formed biofilms can be disrupted by MSC, highlighting the potential for MSC to be used as a treatment for chronic infections, including those often associated with biofilms. 40,41 We also found that MSC produced factors that Production of AMP is one of the most widely investigated direct antimicrobial mechanisms of MSC. 5,18,20,21,42 Previous studies have reported spontaneous production of several different AMP by human and animal MSC, as revealed by bactericidal assays.…”
Section: Discussionmentioning
confidence: 61%
“…However, whether it is of bacterial or environmental (including host) origin (or both) is controversial; certainly it is difficult to determine which is the case under in vivo conditions. Studies using in vitro biofilm models (grown on plastic, glass, or other abiotic surfaces) provide a convenient way to screen large sets of strains, treatments, or growing conditions (44).…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies for wound management have been described previously, including the delivery of growth factors to accelerate healing (8)(9)(10). Magana et al also described in detail the laboratory techniques used to monitor, characterize, and quantify bacterial biofilms (11). The focus of this review article is on infection management strategies for chronic wounds.…”
Section: Introductionmentioning
confidence: 99%